Physical Characterization of Liposomes Formulation Lyophilized in the Presence of Disaccharide and HPMC as Dispersed Matrix - Nur Aini Mulyadi (Trans Tech Publications Ltd, 2017)
The present study focuses on characterization the physical properties of liposome formulation which was dispersed in HPMC matrix and lyophilized in the presence of disaccharides. The lyophilized formulations featured cationic dimethyldioctadecylammonium (DDA) to produce dry solid and overcome limitations in terms of detrimental phase separation in phospholipid membranes during production process. Disaccharides, such as sucrose and lactose, have been reported to protect phospholipid membranes during drying, while HPMC was used as dispersed matrix to inhibit recrystallization of disaccharide. Their physical properties were characterized including their morphology using scanning electron microscopy (SEM), crystallinity using x-ray diffractometry (XRD), and solid phase separation using differential scanning calorimetry (DSC). On the basis of these evaluations it was found that the presence of sucrose and HPMC in the formulation showed a miscible mixture and relatively less crystalline-forming properties compared to those using lactose, thus potentially construct a stable dried liposomal formulation. The present study reveals prospective advantages of using combination of sucrose and HPMC in development of dried–DDA liposomal formulation.